Handbike aerodynamics: Wind tunnel versus track tests - Belloli, M.; Cheli, F.; Bayati, I.; Giappino, S.; Robustelli, F. (Procedia Engineering, 2014)
It is well established that wind resistance is responsible for most of the metabolic cost of cycling in level ground. Aerodynamic drag is about 80% of the total resistive force in road racing at 30 km/h and up 94% in time trial competitions at 50 km/h, so that it becomes very important to reduce it to improve cycling performance and similarly, but less investigated, in handcycling. We have investigated handbike aerodynamics by means of wind tunnel tests to define the drag area in different athlete's positions. We found significant differences between the propulsive stage, when the athlete is pedaling and the purely aerodynamic stage, when the athlete is not pedaling and he has only to minimize his drag, as in a downward slope. Track tests are used to confirm wind tunnel data.